The influence (impact) of the religion on honesty, morality meaning of life and happiness of a man in the awareness (consciousness) of Polish youth = Wpływ religii na kształtowanie postawy opartej na uczciwości, moralności, poczuciu sensu życia i szczęścia w świadomości polskiej młodzieży - Baniak, Józef (Przegla̜d religioznawczy, 2019)
In this article, I present the results of my sociological research on the perception and assessment of the role of religion by Polish youth in the sense of life and people’s happiness. I realized out my own research in 2008 among 456 school youth in Kalisz and in 2011 among 426 students of the College of Communications and Management in Poznan. The results of my research are confronted here with the results of research of other sociologists with they realized (implemented) in the past (XX) century among high school youth and students on the subject of existential role. A comparative analysis of the results of both research showed significant changes in the assessment of today’s (contemporary) Polish youth, which the of religion in giving meaning to life and a sense of happiness for people. Today’s youth (from the 21st century) in Poland is more critical of the existential role of religion and more often questions the necessity of this role in people’s lives than the youth of the past century. At the same time, the indicator of today’s youth has decreased, which accepts fully or conditionally (partially) the role of religion in life and in the feeling of happiness by people. Indicator of positive of the existential role of religion among Polish youth were much greater in the past century.